Freedom of the Press as a Discrete Constitutional Guarantee - Oliphant, Benjamin (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2013)
While “freedom of the press” is explicitly guaranteed in section 2(b) of the Charter, Canadian courts have tended to treat the term as a superfluity to be protected, if at all, through the related but conceptually distinct notion of freedom of expression. This paper argues that the absence of a discrete analytical framework for press freedom fails to give full meaning to the text of the Charter and is inconsistent with the Supreme Court’s own acknowledgment of the vital and unique importance of press freedom within the context of section 2(b). I suggest that the reasons provided for rejecting constitutional protection are typically based on the presumed absence of any workable Charter framework, which the analysis proposed here attempts to supply. To that end, this paper advances a three-step framework for the protection of newsgathering activity and illustrates its operation by applying it to the vexed issue of confidential sources. It concludes by suggesting that adopting a purposive interpretation of press freedom—as a freedom intended to guarantee the public’s “right to know”—would ensure that the Court’s doctrine matches its rhetoric and that this fundamental freedom is no longer treated as a mere constitutional redundancy.